Social Learning Analysis in the Tahfiz Class at SMAN 1 Sidrap - Khaerul Muawan; Sitti Jamilah Amin; Ambo Dalle; Hannani Hannani; Kaharuddin Ramli (Journal on Education, 2025)
This study aims to analyze the social learning that occurs in the Tahfiz class program at SMAN 1 Sidrap, which integrates religious education of the Quran with the formal curriculum. This program was initiated by the school principal, Syamsul Yunus, with the goal of providing a space for students who already have memorized parts of the Quran to continue and deepen their memorization. This study uses a qualitative approach with in-depth interviews with students to explore the social aspects influencing the Tahfiz learning process. The results of the study show that social learning in the Tahfiz class is highly influenced by the interactions between students, the role of teachers, and the physical and social environment around them. Factors such as observation and imitation of learning methods, motivation from peers and teachers, and support from parents play a significant role in improving students' memorization quality. However, there are also challenges such as weak social norms in the class and a lack of positive reinforcement that can reduce intrinsic motivation among students. Therefore, this study recommends enhancing positive reinforcement, developing supportive social norms, and improving the classroom environment to create a more conducive learning atmosphere. Social learning in the context of the Tahfiz class demonstrates that social interaction and environmental support are crucial in supporting the learning and memorization process of the Quran